Densidade populacional de cultivares de soja em solo de várzea: desempenho da cultura e qualidade fisiológica das sementes - Seus, Rogério (2011)
The soybean crop has an important economic partner in the country, because Brazil is a major producer of the grain in the world. Rio Grande do Sul is a state with a grain production characteristic, among them rice and soybeans, with approximately six million hectares of paddy soils, where only one fourth is occupied by rice cultivation, and the rest remain fallow and underutilized. However, we have sought alternatives to the cultivation of these areas, with crops that support the environmental conditions, making it the most profitable areas. The objective of this study was to evaluate the performance of three soybean cultivars, as well as the physiological quality in planossolo seed produced, submitted to five plant populations. The experiment was conducted at Embrapa Clima Temperado in 2008/09 and 2009/10 crop, using five populations (16, 28, 40, 52 and 64 plants per m²) and three cultivars (BRS PampaRR, BRS BRS 246RR and BRS 255RR) arranged in blocks with three and four replications in their respective crop. Significant responses for most variables when subjected to population changes, decreasing the value of these when they population increased. Moreover, with increasing population, variables such as number of nodes, pod and seeds per unit area had increased in value in the branches, while the main stem remained almost flat. This demonstrates first that the effect of number of branches directly influences yield components, and second, the ability to adjust components before different populations. Variables such as seeds per pod and thousand seed weight did not change or contributed little in yield, and the response varies with the population. There was a positive relationship in the yield on the main stem population growth, has branches in the relationship was negative, ranging in 2009/10 crop among cultivars. Overall, the yield in the 2008/09 crop did not change significantly, while in 2009/10 crop there was significant increase in yield with population increase. For the cultivars, most of the variables there was significant response to the 2008/09 crop on the main stem and to the 2009/10 crop on branches, especially in BRS PampaRR and BRS 246RR cultivars, on the other hand the BRS 255RR cultivar stands in the variable thousand seeds weight. The components of yield are directly related to the branches and thus reflected in yield. However, the partial yield (main stem and branches) was not significant difference among cultivars. Thus we can conclude that the environment influences in the yield, as population and cultivars, the component that contributes most in yield is the number of pods, and the components behave differently on the main stem and branches.